Oxidative Stability of Ground Chicken Patties Enhanced with Rosemary Diterpene Phenols Relative to Ascorbic Acid - Naveena, B. M.; Muthukumar, M.; Banerjee, Rituparna; Shaju, V. A.; Ramesh, C. K. (Journal of Meat Science, 2019)
Present study was conducted to optimize natural phenols mixture which can yield the antioxidative effect equivalent to 500 ppm ascorbic  acid (AA) in raw and cooked ground chicken patties stored under refrigeration. Purified rosemary extract (Oxikan-R) with 2.8% carnosic  acid (CA) and 0.55% carnosol has been incorporated into ground chicken patties at 0.05% (low-dose), 0.18% (high-dose) and compared  with 0.05% AA and non-treated control. Oxikan-R and AA are effective (p< 0.05) in limiting the lipid oxidation in both raw and cooked  chicken patties. Protective effects of antioxidants in stabilizing the meat color through reduction (p< 0.05) of % metmyoglobin, % dena tured myoglobin and improved redness scores (a*-value) were observed during storage. Reduction in total plate counts of chicken patties  treated with Oxikan-R compared to control suggested the antimicrobial activity of Oxikan-R. Present study demonstrates the efficacy  of Oxikan-R as a natural alternative to ascorbic acid.
Keywords: Rosemary; Carnosic acid; Carnosol; Chicken Patties; Lipid Oxidation